Breakable Hybrid Organosilica Nanocapsules for Protein Delivery. Issue 10 (8th December 2015) - Prasetyanto, Eko Adi; Bertucci, Alessandro; Septiadi, Dedy; Corradini, Roberto; Castro‐Hartmann, Pablo; De Cola, Luisa
Abstract: The direct delivery of specific proteins to live cells promises a tremendous impact for biological and medical applications, from therapeutics to genetic engineering. However, the process mostly involves tedious techniques and often requires extensive alteration of the protein itself. Herein we report a straightforward approach to encapsulate native proteins by using breakable organosilica matrices that disintegrate upon exposure to a chemical stimulus. The biomolecule‐containing capsules were tested for the intracellular delivery of highly cytotoxic proteins into C6 glioma cells. We demonstrate that the shell is broken, the release of the active proteins occurs, and therefore our hybrid architecture is a promising strategy to deliver fragile biomacromolecules into living organisms. Abstract : Speshell delivery : The construction of a breakable shell around proteins can be used for encapsulation and delivery of functional proteins. The shell comprises silica units that are held together with disulfide bridges. These stimulus‐responsive containers break into very small pieces upon contact with the cell environment, and the proteins retain their activity during encapsulation.